Tetracycline-grafted mPEG-PLGA micelles for bone-targeting and osteoporotic improvement - Que, Yunduan; Yang, Yuhang; Zafar, Hajra; Wang, Dongming (Frontiers in Pharmacology, 2022)
Aim: We aimed to create a nano drug delivery system with tetracycline (TC)-grafted methoxy poly-(ethylene-glycol)‒poly-(D, L-lactic-co-glycolic acid) (mPEG‒PLGA) micelles (TC‒mPEG‒PLGA) with TC and mPEG‒PLGA for potential bone targeting. Prospectively, TC‒mPEG‒PLGA aims to deliver bioactive compounds, such as astragaloside IV (AS), for osteoporotic therapy. Methods: Preparation and evaluation of TC‒mPEG‒PLGA were accomplished via nano-properties, cytotoxicity, uptake by MC3T3-E1 cells, ability of hydroxyapatite targeting and potential bone targeting in vivo, as well as pharmacodynamics in a rat model. Results: The measured particle size of AS-loaded TC‒mPEG‒PLGA micelles was an average of 52.16 ± 2.44 nm, which exhibited a sustained release effect compared to that by free AS. The TC‒mPEG‒PLGA demonstrated low cytotoxicity and was easily taken by MC3T3-E1 cells. Through assaying of bone targeting in vitro and in vivo, we observed that TC‒mPEG‒PLGA could effectively increase AS accumulation in bone. A pharmacodynamics study in mice suggested potentially increased bone mineral density by AS-loaded TC‒mPEG‒PLGA in ovariectomized rats compared to that by free AS. Conclusion: The nano drug delivery system (TC‒mPEG‒PLGA) could target bone in vitro and in vivo, wherein it may be used as a novel delivery method for the enhancement of therapeutic effects of drugs with osteoporotic activity.